Newspapers of Ukrainian SSR of the 1950’s – 1960’s on the Ukrainian Re-Emigration (Trough the Prism of Biographical Studies) - Yu. Shemeta (Vìsnik - Kiïvsʹkij nacìonalʹnij unìversitet ìmenì Tarasa Ševčenka: Ìstorìâ, 2019)
A peculiar phenomenon of post-war life in the Ukrainian SSR was the return of Ukrainian emigrants. Some of them were hoping to improve the economic situation, in particular, to obtain stable earnings and housing. The other part showed active pro-Soviet position. There were analyzed newspapers articles in the of the USSR 1950’s and 1960’s. This was the period of the most intensive movement of the return. The author analyzes the origin, age, social status, political preferences and activity of the re-emigrants from the point of view of the biographical component. It is established that it was residents of Western Ukrainian lands who left from Ukraine before the Second World War the most. Ukrainians went to Europe and America: France, the United States, Canada, but the largest number of them turned out to be in the countries of Latin America, in particular, in Argentina. These were mainly family people who leaved Motherland with their families and had a goal to acquire own land and engage in farming on it. However, the success in agriculture in Argentina, Uruguay, Paraguay and Brazil in those who returned was insignificant due to the difficult working conditions in an unusual climate. Many people were forced to leave the land and work in cities at different jobs. Agricultural workers, workers in industry and services dominated among the re-emirates. Many participated in strikes, the trade union movement, cultural organizations that had contacts with the USSR.